Preparation method and application of graphene aerogel / porous carbon composite electrode for all-vanadium redox flow battery

By filling the graphene gel into the pores of the melamine sponge and carrying out specific process processing, graphene aerogel/porous carbon composite electrode was prepared, which solved the problem of unstable structure of graphene aerogel and significantly improved the energy efficiency of the battery.

CN119812370APending Publication Date: 2025-04-11RUISHENG FLOW BATTERY TECHNOLOGY (QINGDAO) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510232106.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The structure of graphene aerogel is unstable during electrode assembly, resulting in interruption of electron transmission paths, affecting conductivity and stability.

Method used

The graphene aerogel/porous carbon composite electrode is prepared by filling the graphene gel into the pores of the melamine sponge and preparing the graphene aerogel/porous carbon composite electrode through heat treatment, freezing and vacuum processes to enhance its structural stability.

Benefits of technology

It significantly improves the structural stability of graphene aerogel, enhances the electrochemical reaction rate, reduces the polarization of the electrode surface, and improves the energy efficiency of the all-vana flow battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812370A_ABST
    Figure CN119812370A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a graphene aerogel / porous carbon composite electrode for an all-vanadium redox flow battery. The technical problem that an existing graphene aerogel electrode for a redox flow battery is insufficient in structural stability is solved. The preparation method comprises the following steps: S1, fully mixing a graphene oxide dispersion liquid with p-phenylenediamine to prepare a graphene gel reaction liquid; s2, putting the melamine sponge into the graphene gel reaction liquid for dipping, so that pores of the melamine sponge are filled with the graphene gel reaction liquid, and performing heat treatment to prepare graphene / melamine sponge composite gel; s3, the graphene / melamine sponge composite gel is subjected to freezing and vacuumizing treatment, and a graphene aerogel / melamine sponge composite body is prepared; s4, calcining the graphene aerogel / melamine sponge composite body in an oxygen-free atmosphere to prepare a graphene aerogel / porous carbon composite electrode; the method can be widely applied to the fields of battery manufacturing and energy storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery manufacturing and energy storage, and in particular to a method for preparing and applying a graphene aerogel / porous carbon composite electrode for an all-vanadium liquid flow battery. Background Art

[0002] All-vanadium liquid flow batteries have become an ideal choice for large-scale energy storage and have shown broad market prospects due to their excellent safety, long life, high cost-effectiveness, low environmental load, independent design of output power and energy storage capacity, high and uniform power of single battery stacks, flexible and easy expansion of energy storage system design, etc. In particular, in the field of large-scale fixed energy storage applications in power systems, considering the safety of energy storage systems, cost-effectiveness of life cycle and environmental load, all-vanadium liquid flow battery energy storage technology has important market prospects in the future power grid generation side, transmission and distribution side, renewable energy access and distributed power supply and microgrids.

[0003] As one of the three core components of the power unit of a flow battery, the electrode plays a vital role in the entire charge and discharge process of the flow battery. The structural characteristics and surface properties of the electrode material directly affect the electrochemical reaction rate, battery internal resistance and electrolyte transport process, thereby affecting the battery performance. The research and optimization of electrodes are the key to the development of all-vanadium flow battery technology, and its performance directly affects the power density, operating efficiency and cost of the battery. With the continuous advancement of technology, the improvement of electrode materials and structures will continue to drive all-vanadium flow batteries to higher performance and lower costs. At present, in the field of electrode preparation, carbon-based materials (including carbon felt, graphene, carbon cloth and carbon paper, etc.) have been widely used in flow battery electrodes due to their excellent electrical conductivity, corrosion resistance and electrochemical stability. However, in order to further improve the energy efficiency of flow batteries, researchers are exploring how to optimize electrode performance through electrode material modification, structural design and preparation technology innovation.

[0004] Among them, graphene aerogel can provide efficient channels for electron transmission with its three-dimensional network structure and exhibit excellent conductivity. However, due to the instability of the three-dimensional network structure of graphene aerogel, the structure may collapse during the electrode assembly process, which in turn leads to the interruption of the electron transmission path, affecting its conductivity and stability as an electrode material. Summary of the invention

[0005] The purpose of the present invention is to solve the deficiencies of the above-mentioned technology, provide a method for preparing and applying a graphene aerogel / porous carbon composite electrode for an all-vanadium liquid flow battery, and enhance the structural stability of the graphene aerogel.

[0006] The present invention provides a method for preparing a novel graphene aerogel / porous carbon composite electrode for an all-vanadium liquid flow battery. The composite electrode is composed of a graphene aerogel and a porous carbon structure electrode, and comprises the following steps:

[0007] Step S1. Preparing graphene gel reaction solution:

[0008] The graphene oxide dispersion liquid and p-phenylenediamine are fully mixed to obtain a graphene gel reaction liquid.

[0009] Step S2. Preparation of graphene / melamine sponge composite gel:

[0010] The melamine sponge is immersed in the graphene gel reaction solution prepared in step S1, so that the graphene gel reaction solution fills the pores of the melamine sponge, and a graphene / melamine sponge composite gel is obtained after heat treatment.

[0011] In this step, the hydrothermal reduction method is used, and p-phenylenediamine is used as a reducing agent and a cross-linking agent, so that graphene is obtained in the voids of the melamine sponge skeleton through molecular polymerization and cross-linking to form a hydrogel, that is, a graphene / melamine sponge composite gel is obtained.

[0012] Step S3. Preparation of graphene aerogel / melamine sponge composite:

[0013] The graphene / melamine sponge composite gel prepared in step S2 is frozen and vacuumed to prepare a graphene aerogel / melamine sponge composite.

[0014] In this step, the solvent in the hydrogel is removed by low-pressure sublimation without forming a gas-liquid interface. The graphene aerogel prepared in this way has a narrow pore size distribution, a highly ordered porous structure and a certain mechanical flexibility.

[0015] Step S4. Preparation of graphene aerogel / porous carbon composite electrode:

[0016] The graphene aerogel / melamine sponge composite prepared in step S4 is calcined in an oxygen-free atmosphere to obtain a graphene aerogel / porous carbon composite electrode.

[0017] Preferably, in step S1, 2-4 mg / mL of graphene oxide dispersion and 5 mg / mL of p-phenylenediamine solution are mixed at a volume ratio of 25-35:1 and stirred evenly to obtain a graphene gel reaction solution.

[0018] Preferably, in step S2, the density of the melamine sponge is 9.5 to 24 kg / m 3 .

[0019] Preferably, in step S2, the temperature of the heat treatment is controlled at 80 to 95° C., and the time is further preferably controlled at 12 to 24 hours.

[0020] Preferably, in step S3, the freezing temperature is controlled at -14 to -18°C, and the time is further preferably controlled at 6 to 10 hours.

[0021] Preferably, in step S3, the vacuum pressure is controlled at 50-60 Pa.

[0022] Preferably, in step S4, the oxygen-free atmosphere is nitrogen.

[0023] Preferably, in step S4, the calcination method comprises: heating to 280°C at a heating rate of 1°C / min and maintaining the temperature for calcination, and then heating to 1100°C at a heating rate of 5°C / min and maintaining the temperature for calcination.

[0024] Preferably, in step S4, the temperature is increased to 280°C at a heating rate of 1°C / min and kept at this temperature for calcination for 1 hour, and then the temperature is increased to 1100°C at a heating rate of 5°C / min and kept at this temperature for calcination for 6 hours.

[0025] The method described in any one of the above items is used to prepare a graphene aerogel / porous carbon composite electrode for an all-vanadium liquid flow battery and the electrode is used in an all-vanadium liquid flow battery.

[0026] The beneficial effects of the present invention are as follows: the present invention provides a method for preparing and applying a graphene aerogel / porous carbon composite electrode for an all-vanadium liquid flow battery, wherein the graphene gel is filled into the pores of a melamine sponge, and a graphene aerogel / porous carbon composite material is successfully prepared through heat treatment, freezing, and vacuuming processes. Among them, the reducing agent p-phenylenediamine not only plays the role of cross-linking graphene oxide to form a gel, but also significantly enhances the bonding force between the graphene aerogel and the porous carbon through the π-π bond between the porous carbon, thereby greatly increasing the structural stability of the entire composite system. The graphene aerogel / porous carbon composite electrode of the present invention combines the high conductivity and catalytic properties of graphene with the excellent structural stability of porous carbon. Compared with commercial carbon felt electrodes, it significantly improves the energy efficiency of all-vanadium liquid flow batteries; compared with existing graphene gas / porous carbon composite electrodes, it greatly improves the stability of the structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the embodiments of the present invention will be introduced in more detail below in conjunction with the accompanying drawings and specific implementation methods.

[0028] Figure 1 is a process flow chart for preparing a graphene aerogel / porous carbon composite electrode according to an embodiment of the present invention;

[0029] Figure 2a is a sample image of the GF-C-2 composite electrode obtained in Example 2 of the present invention after being compressed, Figure 2 b is a sample picture of the GF-C-4 composite electrode obtained in the comparative example after being compressed;

[0030] Figure 3 a is a scanning electron microscope image of the existing graphene aerogel electrode. Figure 3 b is a scanning electron microscope image of the graphene aerogel / porous carbon composite electrode (GF-C-2) prepared in Example 2 of the present invention;

[0031] Figure 4 The first charge and discharge curves of the all-vanadium liquid flow battery of the GF-C-1, GF-C-2 and GF-C-3 composite electrodes prepared in the embodiments of the present invention and the commercial carbon felt electrode;

[0032] Figure 5 The GF-C-2 composite electrode obtained in Example 2 of the present invention and the commercial carbon felt are used as VO of the all-vanadium liquid flow battery electrode. 2+ / VO2 + CV curve diagram of

[0033] Figure 6 The GF-C-2 composite electrode obtained in Example 2 of the present invention and the commercial carbon felt are used as the V of the all-vanadium liquid flow battery electrode. 2+ / V 3+ CV curve diagram of

[0034] Figure 7 The graphs of cycle number and energy efficiency of all-vanadium liquid flow batteries assembled with GF-C-1, GF-C-2 and GF-C-3 composite electrodes prepared in the embodiments of the present invention and commercial carbon felt electrodes;

[0035] Figure 8 The graph is a graph of the cycle number and coulombic efficiency of an all-vanadium liquid flow battery assembled with the GF-C-1, GF-C-2 and GF-C-3 composite electrodes prepared in the embodiments of the present invention and commercial carbon felt electrodes. DETAILED DESCRIPTION

[0036] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0037] Unless otherwise specified, the methods used in the present invention are all conventional methods; the raw materials and devices used are all conventional commercially available products unless otherwise specified.

[0038] Graphene oxide dispersion was purchased from Qieke New Material Technology (Shanghai) Co., Ltd.

[0039] p-Phenylenediamine solution was purchased from Merck Chemical Technology (Shanghai) Co., Ltd.

[0040] Example 1

[0041] Depend on Figure 1 As shown, Example 1 provides a method for preparing a graphene aerogel / porous carbon composite electrode for an all-vanadium liquid flow battery, comprising the following steps:

[0042] (1) The density is 9.5 kg / m 3 The melamine sponges were cut into cubes of 1 cm × 1 cm × 1 cm and set aside.

[0043] (2) 2 mg / mL of graphene oxide dispersion and 5 mg / mL of p-phenylenediamine solution were mixed in a volume ratio of 25:1 and stirred evenly to obtain a graphene gel reaction solution.

[0044] (3) Soaking the melamine sponge cut in step (1) in the graphene gel reaction solution prepared in step (2), and repeatedly squeezing the melamine sponge to fill the melamine sponge with the graphene gel reaction solution. Then, ultrasonicating the beaker containing the graphene gel reaction solution and the melamine sponge so that the graphene gel can fully enter the pores of the melamine sponge, and the ultrasonication time is controlled at 15 to 30 minutes to obtain a melamine sponge filled with the graphene gel reaction solution.

[0045] (4) Place the melamine sponge filled with graphene gel reaction solution obtained in step (3) into a sealed glass bottle, and then place the sealed glass bottle in an oven, control the temperature at 80-95°C, and control the time at 12-24 hours; after the graphene gel polymerization is completed, take out the sealed glass bottle. After cooling to room temperature, open the glass bottle and take out the sample to obtain a graphene / melamine sponge composite gel, which is placed in an open glass culture dish for standby use.

[0046] (5) placing the graphene / melamine sponge composite gel obtained in step (4) in a refrigerator, controlling the temperature at -14 to -18°C, and controlling the freezing time at 6 to 10 hours; then transferring it to a sealed container for vacuuming, controlling the pressure at 50 to 60 Pa, so that the water in the ice-like composite gel is directly sublimated to obtain a graphene aerogel / melamine sponge composite.

[0047] (6) The graphene aerogel / melamine sponge composite obtained in step (5) is placed in a tubular furnace and calcined under a nitrogen atmosphere. The heating rate is 1°C / min to 280°C and maintained for 1 hour; then the temperature is increased to 1100°C at 5°C / min and maintained for 6 hours. The sample is taken out as a graphene aerogel / porous carbon composite electrode and is labeled as GF-C-1.

[0048] Example 2

[0049] The difference between the preparation method of the graphene aerogel / porous carbon composite electrode in this embodiment and that in embodiment 1 is that in step (1), the density of the melamine sponge is 16 kg / m 3 ; In step (2), 3 mg / mL of graphene oxide dispersion and 5 mg / mL of p-phenylenediamine solution were mixed in a volume ratio of 30:1. The other contents are the same as those in Example 1 and are not repeated here; finally, a graphene aerogel / porous carbon composite electrode was prepared and labeled as GF-C-2.

[0050] Example 3

[0051] The difference between the preparation method of the graphene aerogel / porous carbon composite electrode in this embodiment and that in embodiment 1 is that in step (1), the density of the melamine sponge is 24 kg / m 3 ; In step (2), 4 mg / mL of graphene oxide dispersion and 5 mg / mL of p-phenylenediamine solution were mixed in a volume ratio of 35:1. The other contents were the same as those in Example 1 and are not repeated here; finally, a graphene aerogel / porous carbon composite electrode was prepared and labeled as GF-C-3.

[0052] Comparative Example

[0053] In this comparative example, the preparation method of the graphene aerogel / porous carbon composite electrode is different from that of Example 2 in that the reducing cross-linking agent in the whole process is ethylenediamine. The other contents are the same as those of Example 2 and are not repeated here; finally, a graphene aerogel / porous carbon composite electrode is prepared and marked as GF-C-4.

[0054] Performance Testing:

[0055] 1. Take the graphene aerogel / porous carbon composite electrode (GF-C-2) prepared in Example 2 and the graphene aerogel / porous carbon composite electrode (GF-C-4) prepared in the comparative example, cut the two electrodes into straight cylinders with a bottom diameter of 1 cm and a height of 1 cm, install the samples on the testing machine, start the testing machine to apply dynamic pressure to the samples, and after the two samples are subjected to the same pressure of 1 kPa, the test results are respectively Figure 2 a. Figure 2 As shown in b. Figure 2 As shown in a, the surface morphology of the GF-C-2 composite electrode has basically no obvious change; Figure 2As shown in Figure b, obvious cracks appeared on the surface of the GF-C-4 composite electrode. It can be seen that p-phenylenediamine plays a special role as a cross-linking reducing agent in structural stability; preliminary analysis shows that the reason is that p-phenylenediamine can interact with porous carbon through π-π bonds, making the combination between graphene aerogel and porous carbon in the GF-C-2 composite electrode closer, thereby making the structure of the entire system more stable.

[0056] 2. The scanning electron microscope photos of existing graphene aerogel electrodes are as follows: Figure 3 As shown in a, the scanning electron microscope photo of the graphene aerogel / porous carbon composite electrode (GF-C-2) prepared in Example 2 is as shown in Figure 3 As shown in b. From the electron microscope image comparison, it can be seen that the graphene aerogel in the GF-C-2 composite electrode of the present invention is filled inside with the porous carbon skeleton, and this structure greatly increases the electrochemical specific surface area and conductivity of the existing single porous carbon structure of graphene aerogel as an electrode.

[0057] 3. Assemble the graphene aerogel / porous carbon composite electrodes (GF-C-1, GF-C-2 and GF-C-3) prepared in Example 1, Example 2 and Example 3 and the commercial carbon felt (GF) electrode into all-vanadium liquid flow batteries for standby use. All battery tests were carried out on Arbin BT2000. GF-C-1, GF-C-2, GF-C-3 and commercial carbon felt were the positive electrodes, and the graphite felt electrode was the negative electrode. The positive and negative electrodes used the same electrolyte, both of which were 40 mL of commercial electrolyte; the effective area of ​​the electrode was 4 cm × 4 cm; the current density was set to 60 mA cm -2 ; The charge cut-off voltage is set to 1.55V and the discharge cut-off time is 1.15V.

[0058] (1) Figure 4 The first charge and discharge curves of the all-vanadium liquid flow battery of the GF-C-1, GF-C-2 and GF-C-3 composite electrodes prepared in the embodiments of the present invention and the commercial carbon felt electrode; Figure 4 As shown, the charge and discharge overpotential of the carbon fiber felt (GF) electrode is 0.1356V, and the charge and discharge overpotentials of the composite electrodes GF-C-1, GF-C-2 and GF-C-3 prepared by the present invention are 0.1185V, 0.1125V and 0.1136V respectively.

[0059] It can be seen that, on the one hand, from the overpotential value, it can be seen that the composite electrode GF-C-2 has the smallest overpotential and the best electrochemical performance; on the other hand, from the preparation of the three composite electrodes, the main difference is that the density of the melamine foam is different. After preliminary analysis, the density of the melamine foam is closely related to its microscopic pore structure. When the density is low, the pores formed inside the foam are larger and fewer in number, and the degree of interconnection between the pores is high, showing a loose three-dimensional network structure; with the increase of density, the pore size inside the foam gradually decreases, the number of pores also increases accordingly, and the structure becomes more dense; but when the density is too large, a large amount of graphene aerogel accumulates inside the pores, and even some pores are completely blocked, which reduces the effective contact area between the electrolyte and the composite electrode and the electrolyte flows poorly, which increases the polarization of the battery and reduces the battery capacity and energy efficiency.

[0060] (2) Figure 5 The GF-C-2 composite electrode obtained in Example 2 of the present invention and the commercial carbon felt are used as VO of the all-vanadium liquid flow battery electrode. 2+ / VO2 + CV curve diagram of Figure 6 The GF-C-2 composite electrode obtained in Example 2 of the present invention and the commercial carbon felt are used as the V of the all-vanadium liquid flow battery electrode. 2+ / V 3+ CV curve diagram of .

[0061] Depend on Figure 5 As shown in the figure, both curves have obvious oxidation peaks and reduction peaks, indicating that redox reactions occurred on both carbon felt and GF-C-2 electrodes. The peak current value of the GF-C-2 curve is significantly higher than that of the carbon felt curve, indicating that within the same potential range, the redox reaction rate on the GF-C-2 electrode is faster and more active substances participate in the reaction.

[0062] Depend on Figure 6 As shown in the graph, in the more negative potential region, the absolute value of the current of GF-C-2 is greater than that of the carbon felt curve, indicating that at the same potential, the redox reaction rate on the GF-C-2 electrode may be faster.

[0063] It can be seen that the graphene aerogel / porous carbon composite electrode (GF-C-2) obtained in Example 2 can effectively improve the catalytic activity of the reaction and improve the reaction kinetics of the redox reaction.

[0064] (3) By Figure 7 , Figure 8As shown, compared with carbon felt, the energy efficiency of the all-vanadium liquid flow battery assembled with GF-C-1, GF-C-2 and GF-C-3 composite electrodes is improved, and the energy efficiency remains stable after 50 cycles, and the coulombic efficiency is stable at more than 94.5%, indicating that the modified composite electrode gives the battery good cycle performance, which is beneficial to improving battery life and energy density.

[0065] The present invention provides a preparation method and application of a graphene aerogel / porous carbon composite electrode for an all-vanadium liquid flow battery, which has the following advantages:

[0066] (1) p-Phenylenediamine acts as a cross-linking and reducing agent in the system. It interacts with porous carbon through π-π bonds, which enhances the bonding force between graphene aerogel and porous carbon and greatly increases the structural stability of graphene aerogel.

[0067] (2) The graphene aerogel / porous carbon composite electrode material prepared by the present invention has good catalytic performance, improves the electrochemical reaction rate, reduces the polarization of the electrode surface, and improves the overall energy efficiency of the all-vanadium liquid flow battery. The composite electrode prepared by the present invention has the advantages of high conductivity, large specific surface area, good catalytic performance, good structural stability, etc.

[0068] (3) After graphene aerogel is combined with porous carbon material to form a composite electrode, the overall mechanical properties of graphene aerogel as an electrode can be effectively improved, making it more stable and durable in practical applications.

[0069] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a graphene aerogel / porous carbon composite electrode for an all-vanadium redox flow battery, characterized in that: The steps include: Step S1. Preparing graphene gel reaction solution: The graphene oxide dispersion liquid is fully mixed with p-phenylenediamine to obtain a graphene gel reaction liquid; Step S2. Preparation of graphene / melamine sponge composite gel: The melamine sponge is immersed in the graphene gel reaction solution prepared in step S1, so that the graphene gel reaction solution fills the pores of the melamine sponge, and a graphene / melamine sponge composite gel is prepared after heat treatment; Step S3. Preparation of graphene aerogel / melamine sponge composite: The graphene / melamine sponge composite gel prepared in step S2 is frozen and vacuumized to prepare a graphene aerogel / melamine sponge composite; Step S4. Preparation of graphene aerogel / porous carbon composite electrode: The graphene aerogel / melamine sponge composite prepared in step S4 is calcined in an oxygen-free atmosphere to prepare a graphene aerogel / porous carbon composite electrode.

2. The method for preparing a graphene aerogel / porous carbon composite electrode for an all-vanadium redox flow battery according to claim 1, characterized in that: In the step S1, 2-4 mg / mL of graphene oxide dispersion and 5 mg / mL of p-phenylenediamine solution are mixed at a volume ratio of 25-35:1 and stirred evenly to obtain a graphene gel reaction solution.

3. The method for preparing a graphene aerogel / porous carbon composite electrode for an all-vanadium redox flow battery according to claim 1, characterized in that: In step S2, the density of the melamine sponge is 9.5-24 kg / m 3 .

4. The method for preparing a graphene aerogel / porous carbon composite electrode for an all-vanadium redox flow battery according to claim 1, characterized in that: In step S2, the temperature of the heat treatment is controlled at 80-95° C., and the time is controlled at 12-24 hours.

5. The method for preparing a graphene aerogel / porous carbon composite electrode for an all-vanadium redox flow battery according to claim 1, characterized in that: In step S3, the freezing temperature is controlled at -14 to -18°C, and the freezing time is controlled at 6 to 10 hours.

6. The method for preparing a graphene aerogel / porous carbon composite electrode for an all-vanadium redox flow battery according to claim 1, characterized in that: In the step S3, the vacuum pressure is controlled at 50-60 Pa.

7. The method for preparing a graphene aerogel / porous carbon composite electrode for an all-vanadium redox flow battery according to claim 1, characterized in that: In the step S4, the oxygen-free atmosphere is nitrogen.

8. The method for preparing a graphene aerogel / porous carbon composite electrode for an all-vanadium redox flow battery according to claim 1, characterized in that: In the step S4, the calcination method includes: heating to 280°C at a heating rate of 1°C / min and maintaining the temperature for calcination, and then heating to 1100°C at a heating rate of 5°C / min and maintaining the temperature for calcination.

9. The method for preparing a graphene aerogel / porous carbon composite electrode for an all-vanadium redox flow battery according to claim 8, characterized in that: In the step S4, the temperature is raised to 280° C. at a heating rate of 1° C. / min and kept at this temperature for calcination for 1 hour, and then the temperature is raised to 1100° C. at a heating rate of 5° C. / min and kept at this temperature for calcination for 6 hours.

10. Application of a graphene aerogel / porous carbon composite electrode for all-vanadium redox flow battery prepared by the method according to any one of claims 1 to 9 in all-vanadium redox flow battery.